Has the Philippines forever lost its chance at industrialization? - Williamson, Jeffrey G.; De Dios, Emmanuel S. (2014)
After 1870, and long before the rise of the Asian Tigers and the group of emerging economies of Brazil, Russia, India, China, and South Africa, industrial output grew fast enough in the poor periphery to achieve unconditional convergence on the industrial leaders. The Philippines was part of the group of countries that caught up during the interwar and post-war import-substitution-industrialization years. It began to deviate from the pack after the 1970s, however, leaving the group in 1982, never to re-enter it. This paper examines the possible causes of what appears to have been a unique event. These cover political instability, institutional weaknesses, liberalization policy, labor emigration, and Dutch disease. Taken together, these forces created a “perfect de-industrializing storm”, It seems likely that the Philippines has forever lost its chance at industrialization.
Keywords: Industrialization -- Government policy; Economic development